1996
DOI: 10.1111/1523-1747.ep12329592
|View full text |Cite
|
Sign up to set email alerts
|

Thapsigargin Induces Rapid, Transient Growth Inhibition and c-fos Expression Followed by Sustained Growth Stimulation in Mouse Keratinocyte Cultures

Abstract: Although the sesquiterpene lactone thapsigargin has been shown to possess hyperplastic and tumor-promoting activities when applied topically to mouse skin in vivo, the cellular mechanism(s) which underlie these effects are unclear. We show here that thapsigargin treatment of Primary mouse epidermal keratinocytes increased intracellular free Ca2+ concentration (Cai) in a concentration-dependent manner. Thapsigargin induced a rapid, transient elevation in keratinocyte Cai, in part due to the release of Ca2+ from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…34) It is of interest that Elmets et al 22) demonstrated a significant difference in rates of cutaneous tumorigenesis between different strains of mice and moreover, biphasic effects on cell proliferation and growth inhibition by tumor promoters, such as thapsigargin, 35) okadaic acid, 36) and TPA, 37) have been reported. Thus, it is likely that differences in dose, administration route or mouse strain influence tumorigenesis induced by phytol.…”
Section: Discussionmentioning
confidence: 99%
“…34) It is of interest that Elmets et al 22) demonstrated a significant difference in rates of cutaneous tumorigenesis between different strains of mice and moreover, biphasic effects on cell proliferation and growth inhibition by tumor promoters, such as thapsigargin, 35) okadaic acid, 36) and TPA, 37) have been reported. Thus, it is likely that differences in dose, administration route or mouse strain influence tumorigenesis induced by phytol.…”
Section: Discussionmentioning
confidence: 99%
“…However, an alternative possibility is that the tumors arise in rare cells in which the loss of Atp2a2 heterozygosity has occurred, which would be similar to mechanisms involving known tumor suppressor genes. Thapsigargin, an irreversible inhibitor of SERCA2 activity, serves as a tumor promoter in multistage mouse skin carcinogenesis (10) and has been shown to induce DNA synthesis (11) and cause growth stimulation (12) in cultured keratinocytes. It is unclear, however, whether these effects are due to partial inhibition of SERCA2, which would resemble haploinsufficiency, to complete inhibition, which would resemble loss of heterozygosity (LOH), or to some other effect that is independent of SERCA2.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, because the release of Ca 2ϩ from intracellular storage pools and the entry of extracellular Ca 2ϩ are often coupled, treatment with TG, while blocking Ca 2ϩ accumulation and allowing Ca 2ϩ release from ER, induces a rapid increase of [Ca 2ϩ ] c followed by a sustained increase mediated by a specific Ca 2ϩ influx pathway [Ikari et al, 1997;Wei et al, 1998]. Depending on cell types and treatment protocols, exposure to TG may induce the expression of various genes, including the 78-kDa glucose-regulated protein (GRP78) in Chinese hamster ovary cells [Li et al, 1993] and human rhabdomyosarcoma cells [Delpino et al, 1998], stress proteins in mammalian chondrocytes [Cheng and Benton, 1994], immediate early gene VL30 [Magun and Rodland, 1995] and interleukin-6 in murine macrophages [Bost and Mason, 1995], zinc finger transcription factor, EGR-1, in human melanoma cells [Muthukkumar et al, 1995], c-fos in keratinocytes [Harmon et al, 1996], as well as the growth arrest gene, gadd153, in prostate cancer cells [Lin et al, 1997]. Recently, it has been suggested that TGinduced gene expression in nonexcitable cells is dependent on calcium influx [Rodland et al, 1997].…”
mentioning
confidence: 99%